Assessment of carrying capacity for bivalve mariculture in subtropical and tropical regions: the need for tailored management tools and guidelines - Aubert Anaïs; Aschenbroich Adélaïde; Gaertner Jean‐Claude; Latchere Oihana; Archambault Philippe; Gaertner‐Mazouni Nabila (Reviews in Aquaculture, 2020)
In a context of increasing global food demand, the aquaculture sector, and more particularly bivalve mariculture, has expanded significantly. While the impact of bivalve mariculture was initially overlooked, it is now widely recognized that this industry can significantly impact the ecosystem and its services. Carrying capacity assessment tools have been developed accordingly and have proved to be a useful and efficient aid for mariculture management. However, carrying capacity assessment tools have been mostly designed and implemented in developed temperate countries, while bivalve mariculture is mainly expanding today in tropical and subtropical zones. To what extent the existing carrying capacity assessment tools are suited for use in tropical and subtropical regions has received little attention, and thus constitutes a major issue. The present review aims to fill this gap and highlights the key points to consider for the carrying capacity assessment of bivalve mariculture in tropical and subtropical regions. In line with the requirements for the sustainable development of human activities, and increasing recognition of the need for better integration of social aspects in the management processes, carrying capacity assessment should be undertaken in a more holistic way. Thus, the social, economic and environmental aspects are taken into account in our analysis. A step‐process plan for the sustainable management of bivalve mariculture in tropical and subtropical countries, through the assessment of carrying capacity, is proposed and discussed to offer guidance for managers.